Phase wise implementation of maternity benefit scheme improves maternal and infant mortality rate in Tamil Nadu - Archana, R.; Rani, Devika (International Journal Of Community Medicine And Public Health, 2025)
Health Indices have been the strength of the Tamil Nadu government for a long time. Be it maternal mortality rate (MMR), neonatal mortality rate (NMR) or infant mortality rate (IMR). Tamil Nadu government takes pride in its updated health management information system and the latest data reveal that MMR has reduced from 52.2 per one lakh live births during 2022-2023 to 45.5 during 2023-2024. Similarly, the IMR was brought down from 20.2 to 18.6 and NMR from 14 to 12.7.